+0  
 
0
96
1
avatar

Find all values of x such that   2x/(x + 2) = -6/(x + 4) + 8x/(x + 4).

 Jul 4, 2022
 #1
avatar+124676 
+2

Simplify as

 

(2x) / (x + 2)  =  (8x  -6) / (x + 4)     cross-multiply

 

2x ( x + 4)  =   (8x - 6) ( x + 2)

 

2x^2  + 8x  = 8x^2 + 10x - 12         rearrange as

 

6x^2 + 2x - 12  =  0       divide through by 2

 

3x^2  + x - 6 =   0

 

         -1  ±√ [ 1^2  - 4 * -6  * 3 ]               -1  ±√73

x =   _____________________ =       __________

                   2  *  3                                        6

 

 

 

cool cool cool

 Jul 4, 2022

30 Online Users